MiR-340 Reduces the Accumulation of Amyloid-β Through Targeting BACE1 (β-site Amyloid Precursor Protein Cleaving Enzyme 1) in Alzheimer’s Disease - Tan, Xianpei; Luo, Yi; Pi, Dingfang; Xia, Liexin; Li, Zhilian; Tu, Qiang (Current Neurovascular Research, 2020)
Background: Alzheimer’s disease (AD) is the most common neurodegenerative disease, and the accumulation of amyloid-β is the initial process in AD. MicroRNAs (miRNAs) are widely known as key regulators of the accumulation of amyloid-β in AD. This study analyzed the potential effects and possible internal mechanisms of miR-340 on AD. Methods: The expression of miR-340 in senescence-accelerated mouse prone-8 (SAMP8) mouse and senescence-accelerated mice/resistant-1 (SAMR1) mouse was evaluated by qRT-PCR (quantitative real-time polymerase chain reaction). The expression of β-site amyloid precursor protein cleaving enzyme 1 (BACE1) was determined by qRT-PCR and western blot. The binding ability between miR-340 and BACE1 was verified by dual-luciferase reporter assay. In vitro cell model of AD was established in human neuroblastoma SH-SY5Y cells transfected with Swedish mutant form of amyloid precursor protein (APPswe). The effect of miR-340 on the accumulation of amyloid- β was investigated by western blot analysis. Flow cytometry was conducted to detect cell apoptosis. Results: MiR-340 was down-regulated in the hippocampus of AD model SAMP8 mouse compared to SAMR1 mouse, while BACE1 was up-regulated in SAMP8, suggesting a negative correlation between miR-340 and BACE1 in SAMP8 mouse. MiR-340 could directly bind with BACE1, and over-expression of miR-340 decreased expression of BACE1 in SH-SY5Y/APPswe cells. MiR- 340 reduced the accumulation of amyloid-β and suppressed cell apoptosis through targeting BACE1 in SH-SY5Y/APPswe cells. Conclusion: MiR-340 was downregulated in AD and reduced the accumulation of amyloid-β through targeting BACE1, suggesting a potential therapeutic target for AD.
Keywords: neuronal cell